2006
DOI: 10.1309/40wd3015ch1ryh58
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Study of Gram Stain Competency Assessment in 40 Clinical Laboratories

Abstract: We used a computer-based competency assessment tool for Gram stain interpretation to assess the performance of 278 laboratory staff from 40 laboratories on 40 multiple-choice questions. We report test reliability, mean scores, median, item difficulty, discrimination, and analysis of the highest- and lowest-scoring questions. The questions were reliable (KR-20 coefficient, 0.80). Overall mean score was 88% (range, 63%-98%). When categorized by cell type, the means were host cells, 93%; other cells (eg, yeast), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…False-negative Gram stains could occur due to inadequate specimen or smear preparation or failure to examine an adequate number of fields. In addition, training and maintenance of proficiency for Gram staining remain challenging (5,20). The consolidation of clinical microbiology laboratories has left many community hospitals with limited laboratory capacity.…”
mentioning
confidence: 99%
“…False-negative Gram stains could occur due to inadequate specimen or smear preparation or failure to examine an adequate number of fields. In addition, training and maintenance of proficiency for Gram staining remain challenging (5,20). The consolidation of clinical microbiology laboratories has left many community hospitals with limited laboratory capacity.…”
mentioning
confidence: 99%
“…This can be based on the importance or impact the procedure may have on a patient's clinical management and the potential for serious harm. Microscopy and Gram stain competency assessment is often cited as being one of the more important areas to evaluate because Gram stain misinterpretation can lead to significant patient safety concerns (16). In fact, survey respondents indicated that the most common competency issue requiring remediation was associated with Gram staining and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Competency evaluation of staff members should include measures that allow determination of what the individual knows, what the individual can do, and if the individual actually follows policies and procedures or uses the "know-can-do" approach (10,16). Determining what individuals know and can do is usually straightforward and assesses what they have learned and whether or not they can apply that knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Only appropriate auditing of results and quality control can ensure continued accuracy of the Gram stain methodology in practice [31]. Goodyear et al [32] used a computer-based competency assessment tool for Gram stain interpretation based upon 40 multiple choice questions and assessed the performance of 278 staff from 40 laboratories. The questions proved to be reliable (KR-20 coefficient, 0.80) and the overall mean score was 88% (range, 63-98%).…”
Section: Quality Controlmentioning
confidence: 99%